Tomato Brown Rugose Fruit Virus Nextstrain Build Version 3: Rise of a Novel Clade - Marleen Botermans; Pier P. M. de Koning; Carla Oplaat; Aimee R. Fowkes; Sam McGreig; Anna Skelton; Ian P. Adams; Adrian Fox; Kris De Jonghe; Jill E. Demers; Johanna W. Roenhorst; Marcel Westenberg; et al. (PhytoFrontiers, 2023)
In the Netherlands, tomato brown rugose fruit virus (ToBRFV; genus Tobamovirus) was first identified in tomato crops in 2019. Since then, the National Plant Protection Organization (NPPO-NL) has performed surveys to track and trace this regulated virus aiming for its eradication. To gain more insight in the epidemiology of ToBRFV, genomes were assembled from Illumina sequence data. Whole-genome phylogenetics was integrated with epidemiological metadata in a Nextstrain build. Two new clades were defined, one of which displayed a rapid increase in comparison to the previous version of the Nextstrain build. This rapid increase could be attributed to the unauthorized application of an isolate of ToBRFV as a cross-protection product. Further analysis of the test results of positive samples from tomato production sites suggests that both deliberate application and accidental introduction had occurred. This report introduces the inclusion of 61 new (near) complete ToBRFV genomes in version three of the Nextstrain build, available from https://nextstrain.nrcnvwa.nl/ToBRFV/20220412. [Figure: see text] Copyright © 2023 The Author(s). This is an open access article distributed under the CC BY 4.0 International license.